VALIDITY AND REPRODUCTIBILITY OF THE SANNY SEGMOMETER (Fiep Bulletin - online, 2015)
Introduction: Many authors have written about the importance of the anthropometrics measurements in physical evaluation. The most used measures are the skeleteal breadths, the body perimeters and the skin folds. Among the skeleteal breadths the most used ones are the knee (KB) and elbow breadths (EB) because whit these measures the somatotype can be determinate and wrist breadth (WB). Other measure, usually used, is the length of the superior (LSL) and inferior limbs (LIL). Usually for these measures it is used an paquimeter or a segmometer. Objective the objective of this study is to verify the validity and the reproductibility of Sanny segmometer. Methodology: The data of 50 habitants (25 males and 25 females age between 18 and 36 years old) from the Ribeirão Pires City (SP-Brazil) were analyzed. The group evaluated people underwent to the following procedures: WB, KB, ED, WB, (LSL) and (LIL). These measures were taken through the paquimeter and the Sanny segmometer. The statisct analysis also carried out through the average, standard deviation, Pearson Linear correlation, average standard error and percentual variation between the results from the paquimeter and the Sanny segmometer, besides a percentual evaluation of the results obtained among three different examiners (E1, E2, E3). The measures were taken according to the standarlization procedures. Results and discussions: The found results are:Conclusion: After analysing the obteined results, it was, verified that Sanny segmometer shows an evident REPRODUCTIBILITY and yours utilization is VALID.
Keywords: Segmometer; Body Measuremeant and Antropometry